Penalty shot importance, success and game context in international water polo - Smith, H. K. (Journal of Science and Medicine in Sport, 2004)
To establish the incidence, timing and quantitative importance of penalty shots in water polo and to test whether or not penalty shot success would vary with the context (closeness, quarter, criticality) of the game, official records from six major international tournaments (n= 296 games) were analysed. Across all tournaments, penalties (n= 206) were awarded (1-3 per game) in 51% of games with no difference in frequency between game quarters. Penalty goals (n= 165) comprised only 3.7% of all goals scored, whereas the outcome of penalties (goal/no goal) within each game affected the final outcome (win/loss/tie) of 20% of games. The success rate of penalty shots (80.1%) was not significantly different between games classed as either close or non-close, by a mathematical expression of the running average goal difference up until the time of the penalty, and by the absolute difference of the score at the time of the penalty. Nor was this success rate significantly different between game quarters (72.7, 83.0, 81.5, and 81.8%), or between games classified by their criticality to final tournament placing (80.0, 79.5, and 80.6%, from highest to lowest). Thus, during international water polo, penalties contribute only modestly to game outcome, and penalty shot success is not significantly related to the closeness, quarter, or criticality of the game being played.